2006
DOI: 10.1186/1751-0147-48-3
|View full text |Cite
|
Sign up to set email alerts
|

Summer eczema in exported Icelandic horses: influence of environmental and genetic factors

Abstract: A cross sectional study was designed to estimate the prevalence of summer eczema (a chronic, recurrent seasonal dermatitis) in exported Icelandic horses and the influence of environmental and genetic factors on the development of the disease.Among 330 horses, which had been exported to Germany, Denmark and Sweden, 114 (34.5%) were found to have clinical signs of summer eczema. The prevalence was highest 2 years after export and the exposure to the biting midges Culicoides spp., was found to be the main risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 13 publications
10
57
1
1
Order By: Relevance
“…However, IBH can also occur in the form of an outbreak; the study by Schild, Ferreira and Soares (2003) reported the presence of the disease in 7% of the animals on a property located in Rio Grande do Sul, Brazil. Björnsdóttir et al (2006) found that the greatest risk factor for IBH is exposure to Culicoides biting midges, especially for animals kept on fertilized or humid pastures. In the present study, the two animals imported from the United States (USA) developed the disease one year after arriving in Brazil, and IBH has been shown to be the most common skin allergy in horses in certain regions of the USA (GREINER, 1995;FRIBERG;LOGAS, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, IBH can also occur in the form of an outbreak; the study by Schild, Ferreira and Soares (2003) reported the presence of the disease in 7% of the animals on a property located in Rio Grande do Sul, Brazil. Björnsdóttir et al (2006) found that the greatest risk factor for IBH is exposure to Culicoides biting midges, especially for animals kept on fertilized or humid pastures. In the present study, the two animals imported from the United States (USA) developed the disease one year after arriving in Brazil, and IBH has been shown to be the most common skin allergy in horses in certain regions of the USA (GREINER, 1995;FRIBERG;LOGAS, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the two animals imported from the United States (USA) developed the disease one year after arriving in Brazil, and IBH has been shown to be the most common skin allergy in horses in certain regions of the USA (GREINER, 1995;FRIBERG;LOGAS, 1999). Thus, epidemiological surveys must consider the origin of the animals, especially whether they have been imported, because animals imported from countries such as Iceland, where the presence of Culicoides biting midges has not been reported and the occurrence of this disease has not been described (BJÖRNSDÓTTIR et al, 2006;HALLAMAA, 2009;KNOTTENBELT, 2009), have been shown to be more sensitive than native animals to the development of severe hypersensitivity (BJÖRNSDÓTTIR et al, 2006;HALLAMAA, 2009). The identification of the insect species responsible for the clinical manifestations of IBH described in this study was not possible because the clinical care of the animals took place at a referral center that was far removed from the properties of origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar prevalence of 6.3% was reported for Icelandic horses born in Germany, by Reiher and Bjö rnsdó ttir (2004), whereas Lange et al (2005) found a higher prevalence of 16% among German-born Icelandic horses. The prevalence of summer eczema among horses exported from Iceland to any of these countries is considerably higher: 26% to 72% has been reported (Halldó rsdó ttir and Larsen, 1991;Lange et al, 2005;Bjö rnsdó ttir et al, 2006). Horses born in Iceland are not exposed to Culicoides early in life and will not have the possibility to develop a normal immunity response to its antigen.…”
Section: Prevalencementioning
confidence: 99%
“…The clinical symptoms of IBH include intense itching leading to scratching, hair loss, scaling, thickening of skin, open wounds and secondary infections (Schurink et al, 2011;Bjornsdottir et al, 2006). The clinical symptoms can in general be recognized by horse owners themselves.…”
Section: Clinical Symptomsmentioning
confidence: 99%